The Scope of Regulation of Access to Activities in the Field of Organizing Tourist Events and Facilitating the Purchase of Related Tourist Services in Polish Law. Selected Issues - Maszewski, Łukasz (Review of European and Comparative Law, 2020)
The considerations carried out in this article focus on the scope of regulation of undertaking (access to) activities in the field of organizing tourist events and facilitating the purchase of related tourist services in the part relating to the features of the activity covered by it. Entities operating in this area are subject to specific legal obligations, including requirement for obtaining an entry in the register. Business in question is no longer a regulated activity but the provisions regarding this activity apply to it. This study also deals with the consequences of this seemingly insignificant change in the nomenclature. These issues are presented against the background of EU regulations and selected EU Member States.